Safety and efficacy of a temperature-controlled ablation system for ventricular tachycardia: Results from the TRAC-VT study - Kautzner, Josef; Moreno, Javier; Tondo, Claudio; Anselme, Frédéric; Burrell, James; Becker, Daniel; Peichl, Petr; Patchett, Ian; Dhanjal, Tarvinder (Journal of interventional cardiac electrophysiology, 2025)
BACKGROUND: Catheter ablation using radiofrequency (RF) energy is an established treatment for ventricular tachycardia (VT). Tissue temperature is a key determinant of successful lesion creation, and yet, it is difficult to measure during conventional RF ablation because of the cooling effect of high-flow rate saline irrigation. The TRAC-VT study evaluated the safety and efficacy of a novel irrigated RF ablation system modulating power based on real-time tissue temperature. METHODS: Patients with sustained monomorphic VT and structural heart disease (SHD) were enrolled. Catheter ablation was performed in temperature-control mode (irrigation 8 ml/min, temperature set-points 55 or 60 °C, and power output ≤ 50 W), with RF applications for ≤ 45 s. The primary safety endpoint was a composite of cardiovascular-specific serious procedure-related adverse events within 30 days post-ablation. The primary effectiveness endpoint was acute success (i.e., non-inducibility of all clinically relevant VTs). RESULTS: Thirty-eight patients were enrolled with monomorphic VT (age 68 ± 12 years and 84% male), with an average of 1.7 ± 1.2 VTs targeted per patient. In total, 41 ± 23 RF applications per patient were delivered. Acute procedural success was 100% (95% CI, 91-100%). No primary safety endpoints were observed. Six-month follow-up was completed in 92% of patients with 81% (95% CI, 65-91%) freedom from sustained or treated VT. A repeat ablation was performed in three patients. CONCLUSIONS: Ablation of VT in SHD, using a temperature-controlled irrigated RF catheter, was safe and effective with a low rate of VT recurrence at 6 months.
Keywords: katetrizační ablace; výsledek terapie; Humans; léčebná irigace; ženské pohlaví; design vybavení; Female; Treatment Outcome; Aged; komorová tachykardie; Male; mužské pohlaví; Tachycardia, Ventricular; Therapeutic Irrigation; Catheter Ablation; lidé středního věku; Middle Aged; senioři; lidé; Equipment Design